THE ROLE OF DIALECTS IN SHAPING LITERARY VOICES: A STUDY OF REGIONALISM IN 20TH-CENTURY FICTION - Kour, Banpreet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article analyzes the impact of dialects on regional literature’s construction of voices within 20th century fiction. It looks into the use of dialects as the markers of authenticity and symbols for culture and identity in literature. The scope of the study includes major figures known for their use of dialects such as William Faulkner, Zora Neale Hurston, and Thomas Hardy in order to trace the relation between language and culture. The study assesses readership and literary criticism through the lense of dialectal exposure and focuses on the role of heritage preservation. It also considers the cultural consequences of dialects in literature and how they subvert the dominant linguistic system and provide room for diversity in narratives.